PENGARUH MOTIVASI, PELATIHAN DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI (Studi Kasus Pada Pegawai Badan Pertanahan Nasional Kabupaten Sragen) - Kasworowati, Terate Ayu; Safitri, Unna Ria; Hegy Suryana, Alean Kistiani (Universitas Boyolali, 2023)
The Influence of Motivation, Training and Job Satisfaction on the Performance of Sragen District Land Office Employees. This study aims to determine the effect of motivation, training and job satisfaction on the performance of employees of the Sragen District Land Office. The method or type of this research is a survey, the population or the target are employees at the Sragen District Land Office 121 people. Data collection techniques through questionnaires, and documentation as support. Data analysis was performed using multiple linear regression analysis method. The results of the analysis show that simultaneously (together) the independent variables have a significant and positive influence on the dependent variable. Variables consisting of motivation, training and job satisfaction amounted to 0.000 on the performance of Sragen Regency Land Office employees. And partially the motivation variable is 0.002, training is 0.000, satisfaction is 0.032. Thus the first hypothesis to the last is accepted. To improve the performance of employees of the Sragen National Land Agency, it is recommended to pay more attention to employee performance. The results of this study indicate that work conflict has a negative effect on employee performance which can result in discomfort at work.